PENGARUH DISIPLIN, LINGKUNGAN DAN MOTIVASI KERJA TERHADAP ETOS KERJA ISLAMI DI RS MUHAMMADIYAH PONOROGO - Titah Nurrahma; Titi Rapini; Sujiono (ITB AAS Indonesia Surakarta, 2026)
Islamic work ethic is an important part in improving the quality of health services, especially for nursing staff who have a strategic role in providing direct services to patients. However, various factors such as work discipline, work environment, and work motivation often influence the strength or weakness of the implementation of Islamic work ethic in the hospital environment. This study aims to analyze the influence of Work Discipline, Work Environment, and Work Motivation on Islamic Work Ethic among nursing staff at Muhammadiyah Ponorogo Hospital. The research method used is a quantitative approach with an associative research design. The research sample amounted to 65 nursing staff using a total sampling technique. Data collection was carried out through questionnaires, then analyzed using multiple linear regression with the help of the SPSS program version 25, as well as instrument testing and classical assumption testing. The results of the study indicate that Work Discipline, Work Environment, and Work Motivation have a positive and significant effect on Islamic Work Ethic both partially (t-test) and simultaneously (F-test). The R² value of 0.672 indicates that 67.2% of the variation in Islamic Work Ethic is influenced by these three variables, while the remaining 32.8% is influenced by other variables outside the study. In conclusion, increasing discipline, improving the work environment, and strengthening work motivation have important contributions in shaping the Islamic work ethic of nursing staff at Muhammadiyah Ponorogo Hospital. These findings provide implications for management to strengthen Islamic value-based coaching programs in an effort to improve the quality of hospital services. Keywords: Work Discipline, Work Environment, Work Motivation, Islamic Work Ethic